HSPA5 Inhibitor Meliorate DSS-Induced Colitis through HSPA1A/CHIP. (13th July 2022) - Gao, Fei; Fan, Heng; Xue, Linping; Shou, Zhexing; Zhu, Feng; Yu, Ting; Chu, Si; Wei, Chunzhu; Liu, Chang; Zuo, Dongbo; Zuo, Dongmei
Abstract : Objective . Ulcerative colitis (UC) is closely related to immune response, in which Treg cells (Tregs) suppress the autoimmune response of effector T cells to maintain homeostasis. As a marker of endoplasmic reticulum stress (ERS), HSPA5 was highly expressed in the colon tissue of UC patients. This study is aimed at evaluating the therapeutic effect of HSPA5 inhibitor (HA15) on dextran sulfate sodium- (DSS-) induced ulcerative colitis in mice and explored the effect and related mechanism of HSPA5 inhibitor on the differentiation and function of Tregs. Methods . Thirty-two C57BL/6 mice were randomly divided into four groups (8 mice per group): normal control group, DSS model group, HSPA5 inhibitor (HA15) group (intraperitoneal injection), and dexamethasone (DXM) group (intraperitoneal injection). Except for the blank control group, the other groups were induced with 3% DSS for 7 days and then given corresponding intervention therapy for 7 days. Results . The disease activity index (DAI) score, colon length, histopathological changes, and scores of DSS-induced mice show that HA15 could significantly improve the degree of inflammation in ulcerative colitis. Moreover, HA15 can better inhibit the expression of HSPA5, HSPA1A, and CHIP in the colon and increase the level of FOXP3 mRNA. Finally, the content of Treg cells and the levels of IL-10 and TGF- β 1 were significantly increased, and the levels of IL-6 were significantly reduced. Conclusions . HA15 can improve the differentiation and function of Treg cells by inhibiting the HSPA1A/CHIP pathway, thereby improving ulcerative colitis. Therefore, inhibiting the expression of HSPA5 may serve as a new approach to treat ulcerative colitis.